2019
DOI: 10.1016/j.jmii.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pediculus capitis in schoolchildren in Battambang, Cambodia

Abstract: Primary school children in Cambodia have a high P. capitis infection rate and thus require effective treatment and prevention measures to treat symptoms and lower the infection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…This present study revealed that females had a significantly higher infestation in comparison to the males. In previous studies done in other study areas in Iran more head lice infection was reported in females than males (16)(17)(18). In another study by Zabihi et al, the prevalence of lice infestation in women was reported as more than men, which is consistent with this present study (19).…”
Section: Discussionsupporting
confidence: 92%
“…This present study revealed that females had a significantly higher infestation in comparison to the males. In previous studies done in other study areas in Iran more head lice infection was reported in females than males (16)(17)(18). In another study by Zabihi et al, the prevalence of lice infestation in women was reported as more than men, which is consistent with this present study (19).…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of pediculosis capitis in this study was 68.7% of children in primary schools infested with head lice. This prevalence is quite high compared to studies reported recently in several places, 2.01% in the European Union [26], 12.2% in Riyadh, Saudi Arabia [21], 10% in Barat Daya Iran [25] and 44% in Batambang, Cambodia [27]. Respondents from the researches mentioned previouslty were generally elementary school children in urban areas, where as this research was conducted in rural areas.…”
Section: Discussionmentioning
confidence: 54%
“…Liao et al [22] found that those students aged 10 showed significantly higher infestation than their older fellow students (>10 years old). In the present study, we found that the group of children older than 3 years (preschoolers between 3 and 5 years old) presented a higher infestation rate.…”
Section: Discussionmentioning
confidence: 99%
“…In Battambang, Cambodia, Liao et al [22] examined 323 school children from two primary schools and found that 44.3% were infested with P. capitis. They also determined that girls had significantly higher infestation rates in most age groups (total infection rate: 56.9 % vs. 29.9 %).…”
Section: Discussionmentioning
confidence: 99%